Clinical features of cystic fibrosis patients with rare genotypes. Issue 1 (January 1996) - Castaldo, G; Rippa, E; Raia, V; Salvatore, D; Massa, C; de Ritis, G; Salvatore, F
Abstract : We describe the clinical features of seven cystic fibrosis patients from southern Italy who bear rare genotypes: (1) a patient homozygous for the 2183 AA-->G mutation who was affected by a very early pulmonary form of cystic fibrosis, and five patients who were compound heterozygotes either for the 2183 AA-->G mutation or for the I148T mutation, in both instances with the delta F508 mutation; and (2) a patient homozygous for the early nonsense R553X mutation who showed only a moderately severe form of cystic fibrosis. Our results confirm that environmental or genetic factors unrelated to the CF disease contribute significantly to the development of the phenotype.